2017
DOI: 10.1080/13102818.2017.1302360
|View full text |Cite
|
Sign up to set email alerts
|

StTrxF, a potato plastidic thioredoxin F-type protein gene, is involved in starch accumulation in transgenic Arabidopsis thaliana

Abstract: The plastidic thioredoxin F-type (TrxF) protein plays a key role in plant carbohydrate metabolism. In this work, a gene encoding the TrxF protein, named StTrxF, was successfully isolated from potato and transformed into Arabidopsis thaliana to obtain transgenic plants. Constitutive expression of StTrxF significantly increased the starch accumulation in the transgenic plants. Real-time quantitative polymerase chain reaction analysis showed that constitutive expression of StTrxF upregulated the expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These results suggested that constitutive expression of VvAATP enhanced the starch biosynthesis due to the increased ATP supply into amyloplasts, which further increased the production of precursors (ADPG and G-1-P) and the expression of starch biosynthesis related genes ( Figure 6). The higher level of starch content is related to the increased expression of starch biosynthesis genes [5,[31][32][33][34]. Starch synthase can be grouped into five types, granule-bound starch synthase (GBSS) and four types of soluble starch synthases (SSS): SSS I, SSS II, SSS III and SSS IV [5,6,35].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that constitutive expression of VvAATP enhanced the starch biosynthesis due to the increased ATP supply into amyloplasts, which further increased the production of precursors (ADPG and G-1-P) and the expression of starch biosynthesis related genes ( Figure 6). The higher level of starch content is related to the increased expression of starch biosynthesis genes [5,[31][32][33][34]. Starch synthase can be grouped into five types, granule-bound starch synthase (GBSS) and four types of soluble starch synthases (SSS): SSS I, SSS II, SSS III and SSS IV [5,6,35].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of NtTrxF led to a striking increase of starch accumulation in the leaves of tobacco [1]. The StTrxF/SlTrxF-expressing Arabidopsis plants had higher starch content [8,9]. Wang et al [10][11][12] cloned the SlAATP/StAATP/GmAATP gene from tomato/potato/soybean and found that the transgenic Arabidopsis plants exhibited higher starch content.…”
Section: Introductionmentioning
confidence: 99%